DAMPAK PEMUTIHAN KARANG TERHADAP EKOSISTEM TERUMBU KARANG PADA TAHUN 2010 DI PERAIRAN UTARA ACEH - Muttaqin, Efin; Kamal, Mohammad Mukhlis; Hariyadi, Sigid; Pardede, Shinta; Tarigan, Sukmaraharja; Campbell, Stuart J (Jurnal Teknologi Perikanan dan Kelautan, 2014)
A drastic increasing in Sea Surface Temperature (SST) was happened in Andaman Sea including in Aceh region from April through end of May 2010. The recent escalations of SST have caused mass coral bleaching event in many places in the world including northern Aceh water of Indonesia. Bleaching survey was conducted in Northern Aceh to measure ecological impact of bleaching including bleaching index, coral cover and reef fish abundance. More than 35% bleached coral were died, with tremendous mortality of susceptible genera such as Acropora and Pocillopora. Coral bleaching has impact in declining coral cover in Northern Aceh significantly after coral bleaching and the evidence of loss Acropora in some area. Coral bleaching also impact to coral fishes, where fishes abundance especially coralivorous fishes has declining significantly betwen 2009 and 2011 also 2013. The 2010 bleaching event is one of the most severe events reported for Indonesia including in Northern Aceh.